2020
DOI: 10.2478/agri-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soluble Protein Profile in Cotton Leaves Indicate Rubisco Damage after Treatment with Sumi-Alpha Insecticide

Abstract: The cotton plant suffers from many pests and due to its economic importance, the use of efficient but ecologically friendly pesticides is highly desirable. The insecticide Sumi-Alpha with active compound Esfenvalerate is widely used for cotton treatment in Uzbekistan. This insecticide is considered as moderately hazardous for different organisms of ecosystems, while more collected data and relevant research is a necessity for judgement of their safety and/or potential risk. Therefore, a comparative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As shown in Supplementary Figure S1C , Q/C and Q were linearly related, suggesting that MIP had a single binding site per template molecule. According to formulas ( 1 ) and ( 2 ), Qmax is 3.65 mg/g, and Kd is 47.62 mg/L, which are higher than those in the literature ( 34 ). By comparing the experimental results with those in other literature ( Table 1 ), we concluded that the MIPs have a high adsorption capacity.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…As shown in Supplementary Figure S1C , Q/C and Q were linearly related, suggesting that MIP had a single binding site per template molecule. According to formulas ( 1 ) and ( 2 ), Qmax is 3.65 mg/g, and Kd is 47.62 mg/L, which are higher than those in the literature ( 34 ). By comparing the experimental results with those in other literature ( Table 1 ), we concluded that the MIPs have a high adsorption capacity.…”
Section: Resultsmentioning
confidence: 56%
“…Finally, the mixtures were centrifuged at 5,000 rpm for 3 min, and HPLC was used to determine the concentration in the supernatant to calculate the saturated absorption amount. The adsorption capacity Q (mg/g) of MIP to fenvalerate was calculated using formula ( 1 ). The maximum apparent capacity and binding site were determined by the Scatchard equation ( 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of residual pesticides in the liver of experimental rats A. It was conducted based on the methods recommended by Mamadrakhimov [1].…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…The withdrawal of highly hazardous organophosphate pesticides from the world market over the last ten years has resulted in pyrethroid insecticides becoming the preferred alternative pesticides due to their effectiveness in pest control [ 1 , 2 ]. Pyrethroids have the broadest application, highest efficiency and lowest residue in addition to their moderate toxicity and biodegradability in plants.…”
Section: Introductionmentioning
confidence: 99%